Private Tutoring in English Through the Eyes of Its Recipients - Černá, Monika (My University, 2020)
The individualistic nature of learning nowadays, coupled with the global spread of English, has contributed to the rise of shadow education in English. This study focuses on one of its forms, one-on-one private tutoring in English (PTE); more specifically, it explores this privately purchased service through the eyes of its recipients, learners of English. The aim of this study is to uncover the nature of the PTE that the learners experienced and the perceived role of this type of education in their lives. The study investigates the learners’ lives from early childhood to their entry to university, deploying a narrative interview as a data-gathering instrument. Twenty respondents were interviewed; then the qualitative analysis of the interviews was conducted using open coding. The findings of the study suggest that PTE supplements formal education in the course of the students’ lives. Its role in learners’ lives is linked to remedial or enrichment purposes. Children’s involvement in PTE is initiated either by their parents or by the children themselves for a variety of purposes reflecting all kinds of their needs. Concerning those who provide PTE, they constitute a diverse group including both native and non-native speakers of English; however, nothing is known about them and about the quality of their service. Furthermore, the study identified two specific features of PTE: the demand for PTE for primary school pupils and the phenomenon of the native speaker tutor.
Soukromá výuka angličtiny očima jejích příjemců
Keywords: shadow education; private tutoring in English; one-on-one tutoring; qualitative research; narrative interviews; recipients; stínový vzdělávací systém; soukromé doučování v angličtině; výuka jeden na jednoho; kvalitativní výzkum; narativní rozhovor; příjemce